2018
DOI: 10.1016/j.ijmultiphaseflow.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Annular two-phase flow in vertical smooth and corrugated pipes

Abstract: Two-phase flow in ribbed or corrugated pipes is of interest in many industrial applications. Experiments are performed to assess the flow regime characteristics in upward annular flow through vertical smooth and corrugated pipes. From high speed recordings, the flow regime and temporal film characteristics are obtained. A novel implementation of a planar laser-induced fluorescence (PLIF) method is used to measure the film thickness, preventing strong reflections from deteriorating the measurements. Liquid accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Aliran dua fase vertikal pada pipa bergelombang juga sudah diidentifikasikan dibandingkan dengan pipa tanpa alur. Hasil yang diperoleh menunjukkan perilaku yang berbeda pada kondisi pola aliran yang sama [12].…”
Section: Pendahuluanunclassified
“…Aliran dua fase vertikal pada pipa bergelombang juga sudah diidentifikasikan dibandingkan dengan pipa tanpa alur. Hasil yang diperoleh menunjukkan perilaku yang berbeda pada kondisi pola aliran yang sama [12].…”
Section: Pendahuluanunclassified
“…A thin laser-sheet (< 500 µm) was generated using a frequency-doubled Litron Nd:YAG laser (emission at 532 nm) and LaVision sheet optics, and was directed to the flow at an angle of ≈ 30°through a Ronchi ruling plate that comprised 5 line-pairs per mm and was attached to the correction box. The laser sheet was inclined, rather than being positioned at right angles to the pipe, also in contrast to the work of van Eckeveld et al [44], in order to limit the occurrence of reflections of the intensity-modulated fluorescence by the gas-liquid interface without a prominent shift in the observed pattern. This scenario would ensue, for example, when the interface slope is ≈ 0°(i.e., when the film is flat or in the troughs of any inetrface fluctuations).…”
Section: Apparatusmentioning
confidence: 99%
“…Another noteworthy difference compared to the arrangement used in Ref. [44] is the employment of a Ronchi plate for generating the modulation of the fluorescence emission, which allows us to obtain film thickness measurements with high spatial resolution in the axial direction of the flow. In contrast, the former tracked the deflections (due to TIR) of the shadows cast by a sparse grid that was placed in front of the laser-sheet, resulting in thin dark lines that were separated by much larger bright-emission intervals.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The ribs were positioned in the duct at three various locations to establish three various conditions. It was found that, increasing of the rib height initiated hydro-dynamical instability at lower fluid velocities [Turaihi, et al (2018) and Van Eckeveld, et al (2018)]. Karthikeyan et al (2015), experimentally studied the influence of the rib's height on the heat transfer and fluid characteristics of air flow in a convergent/divergent rectangular channel with an inclination angle of 1° in y-direction.…”
mentioning
confidence: 99%